2011
DOI: 10.1007/s11182-011-9657-5
|View full text |Cite
|
Sign up to set email alerts
|

Conformal transitions of the laurdan molecule in the absorption and fluorescence spectra

Abstract: 535.37 V. Ya. Artyukhov, and B. V. Korolev The fluorescent probe molecule -laurdan (6-dodekanoil-2-dimetilamin naphthalene) -is investigated by experimental and quantum-chemical methods. The influence of the structure non-rigidity on the dipole moments, arrangement of energy levels, and distribution of charges in the laurdan molecule is studied. An optimized structure is obtained and analyzed by the molecular dynamics method. Several structures with different rotation angles of the dimethylamino group are inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The red line in protic polar solvents might therefore be from a planar conformation. The nonplanar conformation, responsible for the blue line, interacts through carbon atoms as well as suggested by other authors [24]. Alcohols are known to exist in nanostructured polar and nonpolar domains; exhibiting nonpolar and polar character that can give rise to different interactions with Laurdan, and thus to multiline spectra [25].…”
Section: Homogeneous Solventsmentioning
confidence: 56%
See 2 more Smart Citations
“…The red line in protic polar solvents might therefore be from a planar conformation. The nonplanar conformation, responsible for the blue line, interacts through carbon atoms as well as suggested by other authors [24]. Alcohols are known to exist in nanostructured polar and nonpolar domains; exhibiting nonpolar and polar character that can give rise to different interactions with Laurdan, and thus to multiline spectra [25].…”
Section: Homogeneous Solventsmentioning
confidence: 56%
“…6 that red lines of all solvents form a class that share some common feature as do the blue lines. Experiments and computational calculations have shown that the higher and lower wavenumber emissions observed in hexane are from nonplanar and planar conformations of Laurdan respectively [24]. In protic polar solvents, Laurdan in planar conformation was shown to interact with the solvent molecule only through its carbonyl oxygen [24].…”
Section: Homogeneous Solventsmentioning
confidence: 99%
See 1 more Smart Citation